Antioxidant activity of mycelia methanolic extracts of endophytic fungi BvFV and BvFIX isolated from leaves of Bauhinia variegata - Freitas Pires, Daniela Gurgel de; Araújo, Laíza Magalhães de; Mesquita, Pedro Góes; Neves, Francisco de Assis Rocha; Borin, Maria de Fátima (Frontiers in Fungal Biology, 2022)
Endophytes are considered an essential source of natural products. Skin is the body’s largest organ; its primary function is the protection of other organs, and aging is one of the most relevant problems associated with this organ. UV radiation generates reactive oxygen species (ROS), which lead to skin degeneration and consequent aging. The main endogenous antioxidants that neutralize ROS are enzymatic antioxidants such as superoxide dismutase (SOD), catalase, glutathione peroxidase, and glutathione reductase, and non-enzymatic antioxidants, such as glutathione and α-tocopherol. Nuclear receptors are involved in molecular mechanisms that control the aging process, especially peroxisome proliferator-activated receptors (PPAR), which regulate the function and expression of genes that modulate the balance between matrix metalloproteinases (MMP) activity and the expression of collagen. Some natural compounds, such as polyphenols, can activate PPAR and reduce the activation of MMP and collagen degradation. In this work, the antioxidant activity of the mycelia methanolic extracts of two endophytic fungi isolated from leaves of Bauhinia variegata, named BvFV and BvFIX, their action as PPAR agonists, and their effect on the activity of antioxidant defense system enzymes were evaluated. The mycelia methanolic extract of BvFV showed a weak agonist effect on PPARβ/δ, a high capability to inhibit lipid peroxidation, increased catalase activity, and increased superoxide dismutase activity by approximately 64%. In contrast, BvFIX increased catalase activity and increased superoxide dismutase activity in a dose-dependent manner, with an increase of 49.62% ± 7.87%, 56.64% ± 12.27%, and 240.46% ± 26.11% at concentrations of 25 µg/mL, 50 µg/mL and 100 µg/mL, respectively, in human dermal fibroblasts submitted to oxidative stress. These results suggest that the metabolites of the mycelia of endophytic fungi studied are promising to act in the chemoprevention of skin aging.